MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER BERBANTUAN QUIZIZZ TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Dwiyana, Almaida; Setiani, Ana; Balkist, Pujia Siti (Universitas Bhinneka PGRI, 2025)
The aim of this research is to compare three different learning models in improving junior high school students' mathematical problem solving abilities. These models include Numbered Heads Together (NHT) assisted by Quizizz, NHT, and direct learning. This research involved 90 class IX students of SMP PGRI 1 Cisolok who were divided into three classes, namely IX A, IXB, and IX C, using a type of quasi-experiment with a Control Group Pretest and Posttest design. The instruments used in this research include test instruments, observation sheets, and documentation. Research findings reveal that there are differences in problem solving abilities between students who use the NHT assisted Quizizz, NHT, and direct learning models. Students with the NHT model assisted by Quizizz are better than students who use the NHT model, students with the NHT model assisted by Quizizz are better than students who use the direct learning model, students with the NHT model are better than those with the direct model.